When we were kings the untold story of the Rumble in the Jungle - Gast, Leon 1936-2021; Alberti, Maryse 1954-; Sonenberg, David; Hackford, Taylor 1944-; Robinson, Keith; Jayanti, Vikram (Universal, 2005)
A documentary on Mohammad Ali at the time of the famous 1974 "Rumble in the Jungle" match with George Forman in Zaire. Includes a music festival featuring America's top African American performers, James Brown and B.B. King
Subtitle from container. - DVD. - DVD release of the 1997 documentary
Widescreen version presented in a matted widescreen format preserving the 1.85:1 aspect ratio of its original theatrical exhibition (full screen and widescreen presentations)
Orig.: USA 1996
Enth. film and cast biographies
Keywords: Ali, Muhammad / 1942-; Foreman, George / 1949-; Foreman, George -- 1949-2025; Ali, Muhammad -- 1942-2016; Geschichte 1974; Boxers (Sports) / United States / Biography; Boxing matches / Angola / Zaire (Province); Boxen; USA; Biografie; DVD-Video